Enhancing Intention to Reuse Based on Perceived Usefulness Mediated by Trust: A Model for Indonesian LinkAja Users - Savira, Dhelvianti Azni; Azzatillah, A.; Rahmadina, Dean Seshar (Golden Ratio of Mapping Idea and Literature Format, 2026)
This research aims to examine how perceived usefulness contributes to the intention to reuse the LinkAja e-wallet, mediated by trust. This research employs a quantitative methodology, targeting members of the Telegram group LinkAja_e-money, and gathered data from 214 respondents through questionnaires. Structural Equation Modeling (SEM) was used to analyze both direct and indirect relationships between variables. Research: The study finds that perceived usefulness significantly impacts both trust and the intention to reuse the LinkAja e-wallet. Moreover, trust exerts a significant effect on intention to reuse and partially mediates the relationship between perceived usefulness and intention to reuse. This study confirms the integral relationships between perceived usefulness, trust, and intention to reuse within the context of LinkAja, offering valuable insights for improving user retention strategies on digital payment platforms.